2014
DOI: 10.1136/annrheumdis-2013-204920
|View full text |Cite
|
Sign up to set email alerts
|

How much does Disease Activity Score in 28 joints ESR and CRP calculations underestimate disease activity compared with the Simplified Disease Activity Index?

Abstract: DAS28-CRP underestimates disease activity when using cut-off points validated for DAS28-ESR; therefore, DAS28-ESR cut-off values should not be applied to DAS28-CRP. Although DAS28-CRP and DAS28-ESR cut-offs for LDA ≤3.2 correspond to SDAI LDA, neither corresponds well to SDAI remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
132
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(147 citation statements)
references
References 18 publications
13
132
0
2
Order By: Relevance
“…Also, DAS28 change scores for REM are only 4–5% higher than for LDA, while those required for SDAI REM are 20% higher than those for SDAI LDA. This all supports the frequent notion that DAS28 REM simply does not reflect a clinical state of REM, but rather a state of LDA 29. When we examined cut points for SDAI that would show at least 80% sensitivity for LDA or REM at 6 months, they correspond quite well to the recently established SDAI 50% and SDAI 70%, minor and moderate, improvement criteria,15 respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Also, DAS28 change scores for REM are only 4–5% higher than for LDA, while those required for SDAI REM are 20% higher than those for SDAI LDA. This all supports the frequent notion that DAS28 REM simply does not reflect a clinical state of REM, but rather a state of LDA 29. When we examined cut points for SDAI that would show at least 80% sensitivity for LDA or REM at 6 months, they correspond quite well to the recently established SDAI 50% and SDAI 70%, minor and moderate, improvement criteria,15 respectively.…”
Section: Discussionsupporting
confidence: 81%
“…However, the extent of the discrepancy between these 2 variants of the same type of score is surprising. In addition, previous studies have shown similar low disease activity response rates when using these DAS28 variants 12. In the current analysis, however, low disease activity response rates were ∼2‐fold higher for the DAS28‐4(CRP) than for the DAS28‐4(ESR).…”
Section: Discussionsupporting
confidence: 41%
“…Alternative DAS28‐4(CRP) cutoff points have been estimated that correspond to the respective cutoff points for the DAS28‐4(ESR) and SDAI 12. As would be expected, lower remission response rates were observed when the alternative, lower cutoff point for remission was used (2.4 versus 2.6); however, the response rates were still substantially higher for the DAS28‐4(CRP) than for the other measures (additional information is available upon request from the corresponding author).…”
Section: Resultsmentioning
confidence: 99%
“…Thresholds for DAS28-CRP RA disease activity categories are systematically lower than the corresponding cutoffs in the DAS28 using the erythrocyte sedimentation rate (ESR) (15,16), as noted in the editorial accompanying Fleischmann and colleagues' article (17). The comparison of MBDA scores versus DAS28-CRP in the article used the DAS28-ESR category thresholds, and therefore yielded more discordance than would have been expected between MBDA categories and DAS28-CRP categories using DAS28-CRP thresholds.…”
Section: To the Editormentioning
confidence: 99%